2022
DOI: 10.3390/nu14020240
|View full text |Cite
|
Sign up to set email alerts
|

Do Overweight People Have Worse Cognitive Flexibility? Cues-Triggered Food Craving May Have a Greater Impact

Abstract: Background: Overweight people have been revealed to have poor cognitive flexibility. Cognitive flexibility reflects proactive and reactive control abilities. However, the impairment had not been explicitly positioned at the cognitive stage. Therefore, this study provides increased support for impairment of cognitive flexibility due to overweight. Method: The study included 34 overweight and 35 normal-weight participants. They were required to complete the food and flower target AX-continuous performance test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This is because the change in eating habits and the type of relationship a person has with food modulates weight control (Davis et al., 2011; Verbeken et al., 2013; Yang et al., 2019). This approach can be done by improving executive functions, emotion regulation, and cognitive flexibility (Eichen et al., 2021; Favieri et al., 2019; Naets et al., 2018; Smith & Whittingham, 2017; Song et al., 2022). In this regard, a large number of studies have been performed, namely, family cognitive‐behavioral interventions (Tsiros et al., 2008), which improve working memory to reduce cravings (Verbeken et al., 2013), and aerobic exercise, which improves the executive functions in children and adolescents (Davis et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the change in eating habits and the type of relationship a person has with food modulates weight control (Davis et al., 2011; Verbeken et al., 2013; Yang et al., 2019). This approach can be done by improving executive functions, emotion regulation, and cognitive flexibility (Eichen et al., 2021; Favieri et al., 2019; Naets et al., 2018; Smith & Whittingham, 2017; Song et al., 2022). In this regard, a large number of studies have been performed, namely, family cognitive‐behavioral interventions (Tsiros et al., 2008), which improve working memory to reduce cravings (Verbeken et al., 2013), and aerobic exercise, which improves the executive functions in children and adolescents (Davis et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found deficits in inhibitory control, working memory, and cognitive flexibility among people with obesity/overweight [4,[6][7][8][9][10][11][12][13]. People with weak executive function have a higher risk of impulsive eating behavior when facing delicious food, and are more likely to focus on the food's appearance and forget about satiety, causing an imbalance between their food intake and body composition [14,15], which finally leads to an increase in body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Given the worldwide increase of the proportion of overweight or obese adults, the development of interventions to modulate food-related brain processes and functions is of great scientific and public interest [ 1 ]. There is a large body of existing evidence that studies the correlation of BMI with neural, behavioral, or psychological parameters [ 2 7 ]. BMI has been also positively associated with food craving [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%